The pathogenesis of post-stroke osteoporosis and the role oxidative stress plays in its development - Li, JinYan; Shi, Lin; Sun, JianMin (Frontiers in Medicine, 2023)
The following criteria are used to determine the appropriate study to study the relationship between stroke and osteoporosis; 1) A comparative study including stroke patients and healthy people;2) To provide the information of bone mineral density (BMD) level in case group and control group at the onset of osteoporosis after stroke;3) Study on the relationship between oxidative stress and stroke and osteoporosis; 4) Research on the present situation and prospect of osteoporosis treatment after stroke; 5) Study on evaluating the correlation between stroke and osteoporosis; and 1) Case-control study in Chinese and English;2) Chinese and English documents on case reports, meeting minutes, abstracts, communications and news developments;3) Research on maxillofacial osteoporosis;4) The data of the conclusion is incomplete; 5) documents that are too old (if necessary).